2015
DOI: 10.1089/chi.2014.0104
|View full text |Cite
|
Sign up to set email alerts
|

Change in Misperception of Child's Body Weight among Parents of American Preschool Children

Abstract: There was a declining tendency among parents to perceive overweight children appropriately. Strategies are needed to explore how to encourage clinician discussions with parents about appropriate weight for their child and strengthen capacity for childhood obesity prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 49 publications
5
27
0
3
Order By: Relevance
“…Burke and colleagues 54 reported conceptually similar findings in the US participants: from 1988 to 2004, a period that was associated with rapid increases in population‐level weight gain in the USA, men and women with overweight or obesity became less likely to identify their weight status as being ‘overweight’. A similar pattern of findings has been reported in longitudinal studies examining weight status misperceptions using other US data, among European adults and in studies that have examined temporal changes in parental underestimation of child overweight status over time 13, 55, 56. These findings indicate that as larger body weights have become more common, the tendency for overweight and obesity to go undetected has increased.…”
Section: Surrounded By Obesity and Failing To See Itsupporting
confidence: 80%
See 1 more Smart Citation
“…Burke and colleagues 54 reported conceptually similar findings in the US participants: from 1988 to 2004, a period that was associated with rapid increases in population‐level weight gain in the USA, men and women with overweight or obesity became less likely to identify their weight status as being ‘overweight’. A similar pattern of findings has been reported in longitudinal studies examining weight status misperceptions using other US data, among European adults and in studies that have examined temporal changes in parental underestimation of child overweight status over time 13, 55, 56. These findings indicate that as larger body weights have become more common, the tendency for overweight and obesity to go undetected has increased.…”
Section: Surrounded By Obesity and Failing To See Itsupporting
confidence: 80%
“…One prediction of this theory is that under‐detection should have become more common as the obesity epidemic has unfolded. In support of this, a number of longitudinal studies have documented that the tendency for individuals with overweight to fail to identify their adiposity and parental underestimation of child overweight have increased concurrently alongside population obesity prevalence 13, 14, 54, 55, 56. Johnson and colleagues examined self‐perceived overweight between 1999 and 2007 in the UK adults and found that during this period of population weight gain, the percentage of individuals with overweight or obesity underestimating their weight status increased.…”
Section: Surrounded By Obesity and Failing To See Itmentioning
confidence: 95%
“…30 Their study treated 2007-2012 as one time block to compare with 1988-1994, rather than examining a more precise biennial trend. Similar analyses were performed for parents' perception about school-aged children (aged 6-11 years) by Hansen et al 37 and preschool children (aged 2-5 years) by Duncan et al, 38 concluding that there was a potential generational shift involving parental body weight perception about their children over the last few decades. In addition, several studies [39][40][41] found that HCP notification about a child's unhealthy weight has increased significantly over time, based on NHANES data obtained between 1999 and 2014.…”
mentioning
confidence: 76%
“…A common assumption is that parental failure to recognise childhood overweight is a major public health concern 79 since parents regulate both what a child eats and his/her opportunities for physical activity. Parental perceptions of child weight status are a key part of many obesity intervention and prevention programs, such as school measurement programmes in the UK and US, in which parents receive feedback about their child’s weight status 10–12 .…”
Section: Introductionmentioning
confidence: 99%